Humaira Choudhry: Pakistan Hajj Medical Mission - Raza, Naeem; Asad, Khalid Hussain; Khan, Abir Mehmood; Ahmed, Salman (Pakistan Armed Forces Medical Journal, 2009)
Objective: To describe constitution, capabilities and functioning of Pakistan Hajj Medical Mission (Pak HMM) in comparison with six other medical missions during Hajj-2008.Study Design: A comparative cross-sectional study.Place and Duration of Study: Pak HMM Hospital, Makkah Mukarramah over a period of 06 weeks during Hajj season-2008.Material and Methods: Besides Pakistan, six other medical missions were visited and their heads requested to answer a specially designed questionnaire prepared in English. Constitution, capabilities and functioning of Pak HMM was compared with other missions. Data was managed and analyzed using computer programme SPSS-10.Results: Pak HMM was selected 12 weeks, whereas other missions were selected 06-24 weeks (mean=16.33+8.62) prior to Hajj season (p=0.66). The doctor: haji ratio at Pak HMM was 1: 1650, whereas it was 1:180-1: 2188 (mean=1:807.16 + 708.56) at other missions (p=0.32). During peak days, average daily out-patient attendance of Pak HMM was 6000, whereas it was 2000-4000 (mean=2833.33 + 816.49) at other missions (p=0.016). Six (85.71%) medical missions including Pak HMM had indoor facilities, routine diagnostic facilities and were able to perform minor surgical procedures under local anaesthesia. Number of fully equipped ambulances for critical evacuation of patients in Pak HMM was none whereas in other missions, it ranged from 0 to 16 (mean=6.33+7.45).Conclusion: Pak HMM is neither selected well in time nor involved in pre-Hajj medical assessment of the intending hujjaj. Although Pak HMM provides health care facilities to Pakistani hujjaj to the best of its capabilities, its indoor facilities, selection and utilization of specialist doctors as well as trained staff and ambulance evacuation of critically sick patients are not adequate.